Global streamers: Placing the transnational at the heart of TV culture. (1st June 2022) - Chalaby, Jean K.
As media globalization has progressed, transnational media have evolved, and this article contends that a new generation has emerged. The first that developed in the latter part of the twentieth century consists of cross-border TV networks and formats. The second is the rise of streaming platforms. During the first generation, the transnational remained a professional practice out of viewers' reach. With the arrival of the second generation, the transnational has become an everyday mode of media consumption and interaction. Online entertainment services have altered the status of the transnational within TV culture, and what was once at the margins now sits at the core. This article theorizes the notion of the transnational before examining the first and second generations of cross-border media. Considering the advent of streaming, it divides the market into three spaces: subscription video on demand (SVoD), advertising video on demand (AVoD) and video sharing. This article demonstrates how transnational consumption makes SVoD platforms more cosmopolitan than cross-border TV networks. Turning to video-sharing platforms ‐ YouTube in particular ‐ it argues that in the history of TV culture this constitutes a shift in status of the transnational by turning a professional practice into a popular one performed by millions. Based on interviews, this article shows how international access lowers the threshold of economic viability for content creators, while users get involved in cross-border conversations through memetic videos and comments. It is no longer place but technology that determines the fate of stories and ideas, and internet delivery has loosened the ties between TV culture and national culture more than ever.